Spatial deformations of osteosynthesis systems. Message 2. Experimental results - М. M. Dyman; M. S. Shidlovskiy; D. G. Odydko; О. P. Zakhovaiko (Mechanics and Advanced Technologies, 2020)
Test procedure and a device for the spatial loading of full-scale bone specimens with fractures and fixation means and simultaneous measurement of mutual displacements arising in the fracture region due to the load are presented. The device allows us to apply longitudinal, transverse bending and rotational one-time and long-term cyclic loads to the specimen, simulating the action of loads when walking. The measurement of displacements was carried out by digitally photographing the fracture areas followed by computer image processing.